2005
DOI: 10.7748/ns2005.04.19.33.46.c3855
|View full text |Cite
|
Sign up to set email alerts
|

Implementing moving and handling in higher education

Abstract: Moving and handling education for staff and students was implemented by one higher education institution and examined across its pre-registration health programmes. This article describes related policy and is of relevance to nurse educators involved in moving and handling, back care advisers and mentors of students in the clinical environment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…In the UK, Higher Education Institutions are legally and professionally required to provide introductory education in patient handling prior to students’ first clinical placement, to be followed by annual updates and clinical teaching within practice placements (RCN 2000, HSC 2004, CSP 2008). The provision of education in patient handling for student nurses within Higher Education Institutions has been well debated (Kneafsey & Smallwood 2010, Felstead & Angrave 2005) and researched in the UK. Nursing students in Jootun and MacInnes (2005) study identified the continued gap between the ‘ideal’ version of moving and handling taught in university and that which occurred in practice.…”
Section: Background and Literature Reviewmentioning
confidence: 99%
“…In the UK, Higher Education Institutions are legally and professionally required to provide introductory education in patient handling prior to students’ first clinical placement, to be followed by annual updates and clinical teaching within practice placements (RCN 2000, HSC 2004, CSP 2008). The provision of education in patient handling for student nurses within Higher Education Institutions has been well debated (Kneafsey & Smallwood 2010, Felstead & Angrave 2005) and researched in the UK. Nursing students in Jootun and MacInnes (2005) study identified the continued gap between the ‘ideal’ version of moving and handling taught in university and that which occurred in practice.…”
Section: Background and Literature Reviewmentioning
confidence: 99%